2015
DOI: 10.1007/s00167-015-3814-2
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of meniscal injuries in US high school athletes between 2007 and 2013

Abstract: Purpose Knowledge of epidemiologic trends of meniscal injuries in young active populations is limited. Better awareness of injury patterns is a first step to lowering injury rates. Our hypothesis was that meniscal injuries in high school athletes would vary by gender, sport, and type of exposure. Methods During 2007–2013, a large nationally disperse sample of US high schools reported athlete exposure and injury data for 22 sports by having certified athletic trainers complete an internet-based data collectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
61
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 33 publications
0
61
0
4
Order By: Relevance
“…The incidence also has been found to be higher in active populations such as military members, in whom the meniscus tear incidence rate was determined to be 8.27 per 1000 person‐years (10 times higher than any documented civilian study) . Acute meniscal tears also occur at higher frequencies during athletic events, reportedly as high as 5.1 per 100 000 athlete exposures in high school‐age athletes .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The incidence also has been found to be higher in active populations such as military members, in whom the meniscus tear incidence rate was determined to be 8.27 per 1000 person‐years (10 times higher than any documented civilian study) . Acute meniscal tears also occur at higher frequencies during athletic events, reportedly as high as 5.1 per 100 000 athlete exposures in high school‐age athletes .…”
Section: Introductionmentioning
confidence: 97%
“…The menisci are fibrocartilaginous structures that contribute to static weight bearing, distributing compressive forces during joint movement, joint lubrication, joint stabilization, and proprioception . Meniscal tears are a commonly occurring musculoskeletal injury across all age and functional groups , with incidental radiographic pathologic changes occurring in the asymptomatic population . The mean annual incidence has been estimated to be as high as 60‐70 per 100 000 knee injuries based on previous reviews .…”
Section: Introductionmentioning
confidence: 99%
“…4 Also, tears of the meniscal body are more common in women than in men. 5 Further, recent epidemiological studies have found that meniscal injury rates are higher in female high school athletes than in males competing in comparable sports, 6 and that females require repeat meniscal repair surgeries 2.2x more frequently. 7 These data suggest that sex hormone levels, including estrogen, may play a role in meniscal injury and repair.…”
Section: Introductionmentioning
confidence: 99%
“…The menisci injury is a common ailment of the knee injury [1]. Due to its hypovascularity and hypocellularity, a meniscus tear does not heal spontaneously [2,3,4] and prolonged untreated damage may lead to the development of osteoarthritis [5,6,7].…”
Section: Introductionmentioning
confidence: 99%